Portrait of the Politicization of Indonesian Bureaucracy in the 2024 Election - Noer, Hamka Hendra (Ridwan Institute, 2024)
This study delves into the intricate relationship between the state and government, with a specific focus on bureaucracy as a pivotal component of government policy. Against the backdrop of political science, the article investigates the politicization of bureaucracy during the 2024 elections in Indonesia. By tracing the historical trajectory of bureaucratic politicization from the New Order to Reformasi, the research sheds light on the evolution of this phenomenon. Emphasizing bureaucratic neutrality as a cornerstone of good governance, the study employs a qualitative-critical descriptive approach through literature reviews. Qualitative data, derived from expert statements and scientific perspectives, undergoes rigorous analysis using discourse and content analysis methods. The historical analysis exposes the enduring link between bureaucracy and politics, notably during the New Order era, characterized by Golkar's absolute dominance. Despite post-1998 bureaucratic reforms, the persistent challenge of bureaucratic politicization looms large, especially in anticipation of the 2024 elections. The research underscores that achieving bureaucratic neutrality encounters obstacles rooted in the political system and socio-political conditions. Conceptual and theoretical discussions, though robust, falter in implementation. Effectuating bureaucratic neutrality mandates stringent adherence to rules, commitment from all bureaucracies, and robust supervision and law enforcement. The imperative for bureaucratic neutrality in the 2024 elections necessitates comprehensive socialization across bureaucracies and active stakeholder engagement, particularly from political parties. Fostering awareness of bureaucratic integrity and neutrality is indispensable for upholding public service duties and advancing the principles of good governance in Indonesia.